Behind the scenes of JAC: the publisher's role. - Orchard, Laura; Jackson, Christopher; Bishop, Phil (Journal of Antimicrobial Chemotherapy (JAC), 2016)
In this brief article, we focus on Oxford University Press's role as the publisher of the JAC and how it supports authors and readers. The article defines the role of the publisher, as opposed to the Editorial team, Editorial Office or Society owner. It reviews three key functions at the publisher, namely, editorial, production and marketing.